The effect of clay content on the relation between uniaxial compressive strength and needle penetration index for clay-bearing rocks - Sair Kahraman; A. Sercan Aloglu; Egemen Saygin; Bilal Aydin (International Journal of Geo-Engineering, 2021)
Abstract The needle penetration index (NPI) test is a non-destructive test that is applicable both in the field and laboratory, and does not require any special sample preparation. This test has been used for the estimation of physico-mechanical properties of soft rocks. In this study, the influence of the clay content on the relation between uniaxial compressive strength (UCS) and the NPI has been investigated for some clay-bearing rocks. The needle penetration tests were carried out at nine different gallery faces during the Cayirhan Coal Mine excavations, and the NPI values were calculated. Claystone, clayey limestone and clay blocks were collected from the locations on which the NPI tests were performed for the determination of rock strength and clay contents. The clay contents and clay fractions of the samples were determined using XRD analysis. A strong correlation has been found between the UCS and the NPI, but some of the data points were scattered. Strong correlations were also found between the NPI and both the total clay content and the smectite content. The UCS values were also strongly correlated to the total clay content and the smectite content. A multiple regression analysis was performed to determine the influence of clay content on the UCS-NPI relation and a very strong model was derived. The correlation coefficient of the multiple regression model is fairly higher than that of the UCS-NPI relation derived by using simple regression analysis. Concluding remark is that the clay content significantly affects the UCS-NPI relation in clay-bearing rocks.